Association between body esteem and sugar-sweetened beverage intake among Chinese undergraduate students: a cross-sectional study - Zhu, Jiawen; Zhu, Yuanyuan; Zhao, Zihe; Huang, Qianling; Liu, Changju; Zeng, Zhi (Frontiers in Nutrition, 2025)
BackgroundHigh intake of sugar-sweetened beverages has been linked to a range of physical, psychological, and emotional issues. Although there were various factors influencing sugar-sweetened beverage intake, the relationship between body esteem and sugar-sweetened beverage intake remains unclear. This study aimed to investigate the association between three dimensions of body esteem (body esteem-appearance, body esteem-attribution, and body esteem-weight) and the likelihood of high sugar-sweetened beverage intake.MethodsA cross-sectional study was conducted among undergraduate students at Nanjing University of Chinese Medicine. Logistic regression analyses were used to assess the association between the three dimensions of body esteem and the risk of high sugar-sweetened beverage intake. Additionally, restricted cubic splines and subgroup analyses were implemented to further explore the associations.ResultsA total of 969 participants were included in the study, with 771 females (79.6%). The mean age of the participants was 20.07 years (standard deviation [SD] = 1.65). After adjusting for covariates, body esteem-appearance was found to be negatively associated with high sugar-sweetened beverage intake (OR = 0.962, 95% CI = 0.935–0.989, p = 0.007), while body esteem-attribution was positively associated with high sugar-sweetened beverage intake (OR = 1.091, 95% CI = 1.046–1.139, p < 0.001). However, no significant association was found between body esteem-weight and high sugar-sweetened beverage intake (p = 0.781). Restricted cubic spline plots showed no non-linear associations between any dimensions of body esteem and the risk of high sugar-sweetened beverage intake (p-nonlinear was 0.912, 0.225, 0.109, respectively). Subgroup analyses revealed no significant interactions.ConclusionThese findings underscored the significance of targeted health promotion strategies and provided references for educational institutions or governmental bodies to steer undergraduate beverage consumption toward healthier patterns.